2008
DOI: 10.1016/j.cub.2008.10.058
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Phytochrome-Interacting bHLH Transcription Factors Repress Premature Seedling Photomorphogenesis in Darkness

Abstract: SUMMARY Background An important contributing factor to the success of terrestrial flowering plants in colonizing the land was the evolution of a developmental strategy, termed skotomorphogenesis, whereby post-germinative seedlings emerging from buried seed grow vigorously upward in the subterranean darkness toward the soil surface. Results Here we provide genetic evidence that a central component of the mechanism underlying this strategy is the collective repression of premature photomorphogenic development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

40
656
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 535 publications
(713 citation statements)
references
References 38 publications
40
656
0
4
Order By: Relevance
“…Plates were wrapped in aluminium foil at 21°C for 6 days in the dark before being The relative abundance of PIF1 and PIF3 levels in cop1 and spa mutants also highlights the differences in the mechanisms of PIF regulation. PIF3 has been shown to be unstable in the cop1-4 and spa123 triple-mutant backgrounds in the dark 23,24,31 , suggesting that COP1 and SPA proteins are necessary for the stability of PIF3 in the dark. In contrast, while PIF1 level is also lower in cop1-4 compared with wild type, PIF1 is much more abundant in the spaQ mutants compared with wild type in the dark (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Plates were wrapped in aluminium foil at 21°C for 6 days in the dark before being The relative abundance of PIF1 and PIF3 levels in cop1 and spa mutants also highlights the differences in the mechanisms of PIF regulation. PIF3 has been shown to be unstable in the cop1-4 and spa123 triple-mutant backgrounds in the dark 23,24,31 , suggesting that COP1 and SPA proteins are necessary for the stability of PIF3 in the dark. In contrast, while PIF1 level is also lower in cop1-4 compared with wild type, PIF1 is much more abundant in the spaQ mutants compared with wild type in the dark (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these experiments were performed under standard seedling growth conditions where seeds are plated in white light and exposed to prolonged saturated white light for inducing complete germination. To examine whether native PIF1 is ubiquitylated in the dark, we grew wild-type seedlings under true dark conditions as previously described 24 , and performed western blots for native PIF1. Results show that the native PIF1 is not ubiquitylated in the dark if the seedlings were grown under true dark conditions (Fig.…”
Section: Cop1mentioning
confidence: 99%
See 1 more Smart Citation
“…In Arabidopsis, PIFs constitute a multiprotein family with seven members, and the developmental roles of individual PIFs in isolation and in combination with other PIF family members have been elucidated in recent years; e.g., through the analysis of a pif1 pif3 pif4 pif5 quadruple mutant (Castillon et al 2007;Leivar et al 2008). These analyses revealed that the individual family members have, at least in part, redundant functions (Castillon et al 2007; Leivar et al 2008). PIF function is also negatively regulated by interactions with light-activated phytochrome B that induce PIF proteolysis in the light (Bauer et al 2004;Park et al 2004;Shen et al 2005).…”
mentioning
confidence: 99%
“…By reverse genetics, we have identified candidate genes to regulators of shade-avoidance responses; ATHB2 orthologs (Ciarbelli et al 2008), photomorphogenesis and seedling establishment; FHY3/FAR1, NDPK2, PIF/PIL family, PP7, RAP1/ ATMYC2, RFI2 (Shen et al 2005;Yadav et al 2005;Chen and Ni 2006;Lin et al 2007;Genoud et al 2008;Leivar et al 2008), light-regulated proteolysis; COP1, EID1, LAF1, SPA1 (Yi and Deng 2005;Marrocco et al 2006;Yang et al 2009;Chen et al 2010;Fankhauser and Ulm 2011) and developmental transitions; CO, PFT1 (Suárez-López et al 2001;Cerdán and Chory 2003) (Table S2). Using the obtained sequence information in a reverse genetics approach, we have identified a novel petunia mutant carrying a mutation in CCT (CO, CO-like, TOC1) domain (Strayer et al 2000;Valverde 2011).…”
Section: Discussionmentioning
confidence: 99%